The financial vulnerability trap: using latent transition analysis to explore the dynamics of consumers' financial vulnerability over time. (4th January 2021) - Hoffmann, Arvid; McNair, Simon; Pallant, Jason
Abstract : Purpose: The purpose of the paper is to examine how psychological characteristics predict membership of and transitions between states of higher vs lower financial vulnerability – and vice versa – over time. Design/methodology/approach: This research uses a dynamic latent class model (latent transition analysis) to explore the dynamics of consumers' financial vulnerability over time using longitudinal data obtained by repeatedly administering a measure of financial vulnerability. Findings: This research finds that consumers in a state of lower vulnerability are "fragile" in having a relatively high likelihood of moving to a state of higher vulnerability, whereas those in a state of higher vulnerability are "entrenched" in having a relatively low likelihood of moving to a state of lower vulnerability. This pattern of results is called the "financial vulnerability trap." While financial self-efficacy explains state membership, the consideration of future consequences drives state transitions. Research limitations/implications: Future research could follow consumers over a longer period and consider the role of alternative psychological characteristics besides those examined. Practical implications: This research provides practitioners with actionable insights regarding the drivers of changes in consumers' financial vulnerability across time, showing the value of financial self-efficacy and the consideration of future consequences when developing strategies to prevent consumers from sliding from a state of lower to higher financial vulnerability over time. Originality/value: There is scant research on financial vulnerability. Further, prior research has not examined whether and how consumers' psychological characteristics help explain their membership of and transitions between states of different levels of financial vulnerability over time.